Related knowledge third trimester pregnant with compliance in the antenatal care (anc) in health inspection kusumabangsa community health centers pekalongan city - Hartono, Mardi; Sari, Yulanda Sispita; Jannah, Miftachul; Anonim, Tri (BAPPEDA Kota Pekalongan, 2017)
In order to reduce the MMR to achieve the MDGs Directorate of Maternal Health has formulated a scenario of accelerating decline in MMR one with antenatal care visits (K1) as much as possible done in the first trimester, in order to encourage increased coverage of antenatal visits four times (K4). Based on preliminary studies obtained K1 coverage in 2015 in Puskesmas Kusuma Bangsa Pekalongan is ranked 10th from K1 coverage for all 14 health centers in Kota Pekalongan 2015 proved 15 (2.1%) of pregnant women who did not visit K1 of 683 Capital pregnant, whereas K4 coverage in Puskesmas Kusuma Bangsa Pekalongan is ranked 13th proven 43 (6.5%) of pregnant women who did not visit K4 of 655 pregnant women. Objective Research to determine Is there a relationship between knowledge of pregnant women Third Trimester with compliance checks Kusuma Bangsa ANC in Puskesmas Kota Pekalongan Antenatal Care is a program that has been planned in the form of observation, education and medical treatment in pregnant women. Pregnant women during pregnancy mandatory minimum 4x ANC visit. Descriptive research design using Kolerasional, sampling techniques Accedental sampling, questionnaires measuring tools, sample of 53 pregnant women Third Trimester. The results of this study using Chi-Square Knowledge pregnant women about the examination of the ANC majority have sufficient knowledge of 39.6%. Compliance in the examination wayward ANC majority of 50.9%, There is a relationship between knowledge of pregnant women Third Trimester with compliance checks 0.348 ANC with significant value the relationship is weak. Conclusion based on the characteristics of the respondents aged 20-35 years as much as 88.6%, junior education as much as 58.5%, did not work (IRT) as much as 58.5%. Suggestions for the respondents expected to be more active in the ANC visit during pregnancy, in order to avoid risks during pregnancy.